2020
DOI: 10.1186/s12916-019-1469-4
|View full text |Cite
|
Sign up to set email alerts
|

Multi-level transcriptome sequencing identifies COL1A1 as a candidate marker in human heart failure progression

Abstract: Background: Heart failure (HF) has been recognized as a global pandemic with a high rate of hospitalization, morbidity, and mortality. Although numerous advances have been made, its representative molecular signatures remain largely unknown, especially the role of genes in HF progression. The aim of the present prospective followup study was to reveal potential biomarkers associated with the progression of heart failure. Methods:We generated multi-level transcriptomic data from a cohort of left ventricular hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 58 publications
3
67
1
3
Order By: Relevance
“…PCR was then amplified using Phusion High-Fidelity DNA polymerase with Universal PCR primers and Index (X) Primers. Finally, the PCR fragments were purified with AMPure XP system again, and each library quality was assessed with the Agilent Bioanalyzer 2100 system (Agilent Technologies, Inc. USA) 46 , 47 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PCR was then amplified using Phusion High-Fidelity DNA polymerase with Universal PCR primers and Index (X) Primers. Finally, the PCR fragments were purified with AMPure XP system again, and each library quality was assessed with the Agilent Bioanalyzer 2100 system (Agilent Technologies, Inc. USA) 46 , 47 .…”
Section: Methodsmentioning
confidence: 99%
“…The clustering for the index-coded samples was carried on a cBot Cluster Generation System by using the TruSeq PE Cluster Kit v3-cBot-HS (Illumina) according to the manufacturer’s specifications. After cluster generation, the libraries were sequenced with the paired-end 150 bp reads model on an Illumina HiSeq X Ten platform 46 , 47 .…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, we used Seurat ( Stuart et al, 2019 ) to identify the marker genes of cell groups by calling differentially expressed genes (DEGs) between the cells of each sub-group and the remaining cells. DEGs were selected if the fold change of log2-transformed expression level was > 1 and p < 0.05 ( Xu et al, 2012 ; Hua et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Experiments show that expression of FAP (fibroblast activation protein alpha) [66], THBS4 [67], CD27 [68], LEF1 [69], CTHRC1 [70], ESR1 [71], CXCL9 [72], SERPINA3 [73], TRPC4 [74], F13A1 [75], PIK3C2A [76], KCNIP2 [77] and GPR4 [78] contributed to myocardial infarction. MFAP4 [79], ALOX15 [80], COL1A1 [81], APOA1 [82], PDE5A [83], CX3CR1 [84], THY1 [85], GREM1 [86], FMOD (fibromodulin) [87], NPPA (natriuretic peptide A) [88], LTBP2 [89], LUM (lumican) [90], IL34 [91], NRG1 [92], CXCL14 [93], CXCL10 [94], ACE (angiotensin I converting enzyme) [95], CFTR (ystic fibrosis transmembrane conductance regulator) [96], S100A8 [97], S100A9 [97], HP (haptoglobin) [98] [162], Zhang et al [163] and Chen et al [164] study indicated that the expression of CCL22, CCR1, FPR1, KNG1, CRISPLD2, CD38 and GPRC5A were linked with progression of ischemic heart disease. Li et al [165] showed that STEAP3 expression can be associated with cardiac hypertrophy progression.…”
Section: Discussionmentioning
confidence: 99%